Influence of Intestinal Microbiota Transplantation and NleH Expression on Citrobacter rodentium Colonization of Mice - Wang, Gaochan; Feuerbacher, Leigh Ann; Hardwidge, Philip R. (My University, 2018)
The intestinal microbiota plays an important role in regulating host resistance to enteric pathogens. The relative abundance of the microbiota is dependent upon both genetic and environmental factors. The attaching and effacing pathogens enteropathogenic Escherichia coli, enterohemorrhagic E. coli, and Citrobacter rodentium cause diarrheal disease and translocate type III secretion system effector proteins into host cells to inhibit pro-inflammatory host responses. Here we determined the influence of both the intestinal microbiota and the expression of the C. rodentium NleH effector on C. rodentium colonization in different mouse models. We performed fecal transplantation experiments between C57BL/6J and C57BL/10ScNJ mice and found that such microbiota transfers altered both the host resistance to C. rodentium infection as well as the benefit or detriment of expressing NleH to C. rodentium intestinal colonization.
Citation: Wang, G.; Feuerbacher, L.A.; Hardwidge, P.R. Influence of Intestinal Microbiota Transplantation and NleH Expression on Citrobacter rodentium Colonization of Mice. Pathogens 2018, 7, 35.
Keywords: Citrobacter; Colonization; Microbiota